Public Relations : An Easy, Step-by-step Guide to Creating a Public Relations Plan. - Wigglesworth, Pamela. (BookBaby, 2014)
In this eBook, Public Relations, An easy, step-by-step guide to creating a small business public relations and media plan, you will find a step-by-step guide for creating publicity for your business without having to hire a PR firm. Learn what public relations (PR) is and isn't and discover how you can make PR part of your marketing strategy.